FRI0426 High Prevalence of Overweight and Obesity in Recently Diagnosed Systemic Lupus Erythematosus Patients in an International Registry. (10th June 2014) - Zen, M.; Parker, B.; Urowitz, M.B.; Bruce, I.N.
Abstract : Objectives: To examine the prevalence of overweight and obesity in a cross-sectional cohort of early SLE patients and to determine factors associated with overweight in this population. Methods: The Systemic Lupus International Collaborating Clinics (SLICC) Inception Cohort (diagnosed <15 months) enrolled SLE patients from 30 centres across 11 countries from 2000 onwards. Clinical, therapeutic and laboratory data were collected according to a standardised protocol. Using data from the enrolment visit, univariate analysis and multivariate regression were used to assess the relationship of individual variables with body mass index (BMI). Results: 1446 patients were studied. There were 1297 (89.7%) women, and at enrolment the cohort had a mean (SD) age and disease duration of 35.2 (13.4) years and 23.9 (17.9) weeks respectively. 593 patients (41.0%) had a BMI≥25 kg/m 2 including 248 (17.1%) who were obese (BMI≥30 kg/m 2 ). The prevalence of BMI≥25 kg/m 2 amongst ethnicities varied and was 46.3% in Caucasians (294/634), 56.6% in those of African Ancestry (123/218), 11.8% in Koreans (20/169), 45.3% in Hispanics (108/238). In a multivariable analysis, BMI≥25 was independently associated with age (OR 1.02, 95% CI 1.004, 1.03), hypertension (OR 1.87, 95% CI 1.34, 2.62), African ancestry (OR 2.66, 95% CI 1.48, 4.77) and Hispanic race/ethnicity (OR 1.62, 95% CI 1.01, 2.60). Overweight patients were also more likely to have fasting hyperglycemia (OR 1.46, 95% CI 1.08, 1.97) and the Metabolic syndrome (OR 2.35, 95% CI 1.83, 3.03). No association with disease activity, therapy or self-reported physical activity was found. Conclusions: In a relatively young, recently diagnosed SLE cohort being overweight was a common cardiovascular risk factor and seemed not to be associated with steroid use. Increased weight is associated with additional CV risk factors in the context of SLE and so should be a target for intervention in this high risk population. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3158